Wild Fish and Expected Utility - Fischer, Bob (Bangladesh Journal of Bioethics, 2017)
Its difficult to process the number of fish killed annually by the fishing industry. Nevertheless, governments are encouraging people to eat even more fishsee, e.g., the USDA dietary guidelinesand although animal advocates certainly dont concur with this advice, they generally havent prioritized fish in their lobbying efforts. Given the influence of utilitarianism on animal advocacy, the odds are good that this is motivated by an expected utility calculation. For those concerned about fish, is there any way to defend them against this calculation? I argue for an affirmative answer: once you factor in an asymmetry between fishing and terrestrial animal agriculture, the expected utility calculation comes out in favor of devoting resources to reducing fishing.